LEGAL IMPLICATIONS OF CONSUMER PROTECTION IN ISLAMIC FINANCIAL PRODUCTS FOR INDONESIA'S ECONOMIC STABILITY: A LITERATURE REVIEW - Sapta Nur Fallah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyse the legal implications of consumer protection in Islamic financial products on Indonesia's economic stability through a literature review. Regulations such as Law No. 8 of 1999 on Consumer Protection and Law No. 21 of 2008 on Islamic Banking have provided a strong legal foundation to protect consumer rights, encourage transparency, and increase public confidence in the Islamic financial industry. The implementation of these regulations is also supported by the role of the Financial Services Authority in supervision, education, and dispute resolution between consumers and financial services businesses. The study results show that effective legal protection of Islamic financial products contributes significantly to economic stability, among others through increasing financial inclusion, strengthening public confidence, and encouraging real sector growth with the principles of fairness and transparency. However, challenges are still encountered, such as low Islamic financial literacy in the community and limited human resources and adequate information technology.